Avoiding the void: cell-to-cell spread of human viruses. - Sattentau, Q (2008)
The initial stages of animal virus infection are generally described as the binding of free virions to permissive target cells followed by entry and replication. Although this route of infection is undoubtedly important, many viruses that are pathogenic for humans, including HIV-1, herpes simplex virus and measles, can also move between cells without diffusing through the extracellular environment. Cell-to-cell spread not only facilitates rapid viral dissemination, but may also promote immune evasion and influence disease. This Review discusses the various mechanisms by which viruses move directly between cells and the implications of this for viral dissemination and pathogenesis.